Wideband flush-mounted surface wave antenna of very low profile - Chen, Zhuozhu (2015)
This paper presents the design of a compact and wideband surface wave antenna that exhibits very low profile and can be flush-mounted on a conformal platform. The proposed antenna comprises a tapered grounded ceramic slab, a unidirectional surface wave launcher, and a tapered impedance transition. The ceramic slab is smoothly tapered to transform the guided surface wave into radiated space wave over a wide frequency range. The surface wave launcher employs a probe-fed parallel plate waveguide with a modified parabolic reflecting wall and a metallic post, which are critical for effectively transforming the cylindrical waves to a unidirectional plane wave within a broad frequency range. Simulated results show that the proposed surface wave antenna achieves a wide operation bandwidth from 6.1 to 18 GHz with a thickness of only 0.12λ0 at the center frequency. Acceptable gain values with stable and quasi end-fire radiation beams are obtained over the entire frequency band. A prototype of the proposed antenna is fabricated and tested. Measured results are in good agreement with simulated ones.